Do lúdico ao pedagógico: vivências teatrais na formação pessoal e profissional dos docentes em serviço - Santos, Eneila Almeida dos (2008)
This research is a continuing education for teachers based on theatrical experiences, games and ludic activities that aim at not only developing teachers professionally, but also personally and socially, that is; it searches for the fullness in a continuing education process; that ruptures with the traditional model of formative practices and stimulates participants to achieve a better performance even with so many irregularities and demands in the current context of education. Based on some categories such as: relationships, collectivity, perception, concentration, challenges, role-plays, spontaneity, integration and transformation, a theatrical experience structure was elaborated, and such experiences established a relationship between the needs of the teachers and what the theatrical art, from some of its rules and principles, can contribute in this formative process. The methodology utilized came from a participant observation, called research-action, which attempted to work problematic foci in the continuing education of teachers in their work environment. Its theoretical fundament is distributed in the two first chapters, which deal with the permanent education of teachers, mainly supported in the thoughts of the educator Nóvoa, and the ludic formation on the context of education, based on the teachings of Spolin and Boal. The theatrical actions are detailed in the last chapter, split into three phases oh execution, amounting to a total of 37 formative experiences developed by eight high school teachers during the HTPC (Collective-Pedagogic Activity Schedule). These ludic interventions in the in-service continuing education of teachers served as stimuli, challenges, wake-up calls, so that the participant teachers would analyze their practices, reflect on them, assuming and searching for solutions compatible to their problems